2020
DOI: 10.3389/fncel.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Arid1a Promotes Neuronal Survival Following Optic Nerve Injury

Abstract: Trauma or neurodegenerative diseases trigger the retrograde death of retinal ganglion cells (RGCs), causing an irreversible functional loss. AT-rich interaction domain 1A (ARID1A), a subunit of the SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex, has been shown to play crucial roles in cell homeostasis and tissue regeneration. However, its function in adult RGC regeneration remains elusive. Here, we show that optic nerve injury induces dynamic changes of Arid1a expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…We identify that Neurod1 and Fezf2 are functional downstream targets of Arid1a to regulate neural differentiation. As currently there is no commercially available ARID1A antibody for chromatin immunoprecipitation analysis of tissues, we analysed the ChIP-seq and ATAC-seq data for ARID1A deposited in public databases from embryonic stem cells 30,31 and retinal ganglion cells 35 and found that Arid1a has enrichment on Neurod1 and Fezf2 loci which support our identification ARID1A directly regulates Neurod1 and Fezf2 in the nervous system. To our surprise, our results showed that the expression of Brg1, the central ATPase subunit of SWI/SNF, was significantly down-regulated after Arid1a deletion.…”
Section: Overexpression Of Neurod1 or Fezf2 In Arid1a Cko Nspcs Rescues The Neural Differentiation Defect In Vitrosupporting
confidence: 70%
“…We identify that Neurod1 and Fezf2 are functional downstream targets of Arid1a to regulate neural differentiation. As currently there is no commercially available ARID1A antibody for chromatin immunoprecipitation analysis of tissues, we analysed the ChIP-seq and ATAC-seq data for ARID1A deposited in public databases from embryonic stem cells 30,31 and retinal ganglion cells 35 and found that Arid1a has enrichment on Neurod1 and Fezf2 loci which support our identification ARID1A directly regulates Neurod1 and Fezf2 in the nervous system. To our surprise, our results showed that the expression of Brg1, the central ATPase subunit of SWI/SNF, was significantly down-regulated after Arid1a deletion.…”
Section: Overexpression Of Neurod1 or Fezf2 In Arid1a Cko Nspcs Rescues The Neural Differentiation Defect In Vitrosupporting
confidence: 70%
“…The relationship between ARID1A alterations or expression loss with the activation of JAK/STAT signaling pathway, especially STAT3 signaling, had also been explored in the published researches. Peng et al (2020) discovered the function of ARID1A expression loss as the regulator for the related genes of STAT3 signaling pathway and resulted in the impairment of apoptosis via the activated STAT3 signaling. In addition, Fang et al (2015) proved that the ARID1A expression loss contributes to the tumorigenesis and development of HCC via activating the STAT3 signaling pathway and NF-κB signaling pathway.…”
Section: Jak/stat Signaling Pathwaymentioning
confidence: 99%
“…In addition, hepatocyte-speci c Arid1a knockout could result in mouse steatohepatitis and tumor development [20]. ARID1A plays important roles in tissue homeostasis and regeneration [21][22][23]. Nevertheless, it remains unclear whether ARID1A de ciency is implicated in pancreatitis and tissue regeneration after injury.…”
Section: Introductionmentioning
confidence: 99%